2004
DOI: 10.1590/s0100-29452004000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estabelecimento e multiplicação in vitro de Pyrus calleryana D-6 em sistema de cultura 'dupla-fase'

Abstract: Este trabalho objetivou estabelecer e propagar in vitro o porta-enxerto de pereira Pyrus calleryana D-6. Os explantes foram retirados de plantas-matrizes e submetidos à desinfestação com imersão em álcool a 70% por dois minutos, seguido de solução de hipoclorito de sódio a 1,5% + Tween 20 por 20 minutos, e após inoculados em meio MS com BAP (4,4 µM), AG3 (0,3 µM) e ANA (0,05 µM). Na fase de multiplicação, as microestacas caulinares, contendo 2-3 gemas, foram transferidas para frascos com 50 mL de meios MS e MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…BAP is responsible for cell division, overcoming apical dominance, and induction of the proliferation of axillary buds (MOK et al, 2000). The present results are similar to those observed by Moraes et al (2004) in Pyrus calleryana D-6 and Radmann et al (2011) in the rootstock 'Flordaguard' (Prunus persica L. Bastch). Both studies found that in the absence of BAP, the emission of new shoots does not take place, creating a dependency on the addition of exogenous cytokinin for the induction of shoots in these two Rosaceae species.…”
Section: +supporting
confidence: 88%
See 1 more Smart Citation
“…BAP is responsible for cell division, overcoming apical dominance, and induction of the proliferation of axillary buds (MOK et al, 2000). The present results are similar to those observed by Moraes et al (2004) in Pyrus calleryana D-6 and Radmann et al (2011) in the rootstock 'Flordaguard' (Prunus persica L. Bastch). Both studies found that in the absence of BAP, the emission of new shoots does not take place, creating a dependency on the addition of exogenous cytokinin for the induction of shoots in these two Rosaceae species.…”
Section: +supporting
confidence: 88%
“…However, they are limited by factors of the physical and chemical microenvironment in the growing containers, such as concentrations of nutrients and growth regulators that can endanger the formation of shoots and/or microplants (BOMMINENI et al, 2001;REED, 2002;CASANOVA et al, 2008). Consequently, the quantity and balance of growth regulators, carbohydrates, and other nutrients are determining factors in the success of in vitro multiplication of plant material (BELL; REED, 2002;RUZIC et al, 2008;MORAES et al, 2004;DOBRÁNSZKI;TEIXEIRA DA SILVA, 2010), as demonstrated by the results in this study.…”
Section: Discussionmentioning
confidence: 57%
“…3A and 4B. The double-phase culture medium is widely used in in vitro culture systems as it is more efficient for many species such as pear rootstock (Moraes et al 2004), and apple rootstock (Machado et al 2004). Surakshitha et al (2019) reported that the major physiological disorder observed during in vitro culture of woody plant species is shoot-tip necrosis (STN).…”
Section: Effect Of Culture Medium On Shoot Proliferationmentioning
confidence: 99%
“…Another factor that can contribute to increasing the multiplication rate and growth of explants is the use of 'double-phase' medium, as described for species of the genus Pyrus spp. (Rodríguez et al 1991, Kadota et al 2001, Moraes et al 2004 and Ananas sp. (Scherwinski-Pereira et al 2012).…”
Section: Introductionmentioning
confidence: 99%